PARTISIPASI MASYARAKAT DALAM KEGIATAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERKOTAAN DI KELURAHAN TELING TINGKULU - Meily N. Welang; Oktavianus Porajouw; Esry H. Laoh (COCOS, 2016)
ABSTRACTThe study aims to describe the community participation in the activities of the National Program for Community Empowerment in Urban Village TelingTingkulu.Researchers took data onTalud development activities in the Village TelingTingkulu.This study was conducted over 6 months,since november 2015 until the month of May 2016.The data used in this research is secondary data, the data obtained from the district office TelingTingkulu and primary data were retrieved through a list of questions or keusioner.Analysis of the data used in this research is descriptive analysis in tableand text.The results showed that community participation in the planning stages in the PNPM activities that exist in the Village TelingTingkulu classified as active by providing feedback and suggestions about the activities that will be created.While community participation in the implementation phase of the community to contribute through energy, building materials, administration and even soil and plants they have.Key Word : Participation, PNPM, Teling Tingkulu